2018
DOI: 10.1002/acm2.12283
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of individualized optimal positioning selection for left‐sided whole breast radiotherapy: DIBH or prone

Abstract: The deep inspiration breath hold (DIBH) and prone (P) position are two common heart‐sparing techniques for external‐beam radiation treatment of left‐sided breast cancer patients. Clinicians select the position that is deemed to be better for tissue sparing based on their experience. This approach, however, is not always optimum and consistent. In response to this, we develop a quantitative tool that predicts the optimal positioning for the sake of organs at risk (OAR) sparing. Sixteen left‐sided breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…It was found that larger total lung volume increase predisposed to more significant DIBH-related heart and LAD dose reductions. Lin et al found that in comparison to FB, DIBH resulted larger benefit in heart and LAD doses during postmastectomy RT than during WBI [ 27 ]. No similar relationship could be seen in our study; in this patient cohort heart and LAD dose reductions were weakly correlated with DIBH-related lung volume increases, and none of the studied parameters seemed to have predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that larger total lung volume increase predisposed to more significant DIBH-related heart and LAD dose reductions. Lin et al found that in comparison to FB, DIBH resulted larger benefit in heart and LAD doses during postmastectomy RT than during WBI [ 27 ]. No similar relationship could be seen in our study; in this patient cohort heart and LAD dose reductions were weakly correlated with DIBH-related lung volume increases, and none of the studied parameters seemed to have predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that a longer cardiac contact distance, the higher the heart dose. Lin and colleagues 10 investigated a variety of anatomical factors in 16 patients including breast and heart volumes and heart in field and reported that the development of a predictive model is challenging for these patients. Similarly, Ledsom et al 9 and Czeremszynska et al 6 could not identify specific characteristics or thresholds that could accurately identify patients who would benefit most from DIBH despite finding correlations between patient related and dosimetric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…stage, smoking status, co-morbidities and radiation prescription. DIBH technique-specific factors investigated in previous studies as potential factors associated with reduction in heart and lung dose were also collected, 6,[8][9][10][11][12][13][14][15][16][17][18] and are provided in Table 2. Multiple heart, lung and LAD doses were recorded from both the FB and DIBH plans ( Table 2).…”
Section: Treatment Planningmentioning
confidence: 99%
See 2 more Smart Citations